Peripheral venous pressure accurately predicts central venous pressure in the adult Fontan circulation. (1st March 2021) - Tan, Weiyi; Small, Adam; Gallotti, Roberto; Moore, Jeremy; Aboulhosn, Jamil
Abstract: Background: Patients with the Fontan circulation lack a subpulmonary ventricular pump and thus the main driver for pulmonary blood flow is a high central venous pressure. Peripheral venous pressure (PVP) measurement has been shown to be a reproducible and fairly accurate surrogate for central venous pressure (CVP), but not specifically for the adult Fontan circulation. This study aims to determine the relationship of PVP to CVP in adult Fontan patients. Methods: All adult patients (≥18 yo) with a Fontan circulation undergoing cardiac catheterization were included. Both CVP and PVP were measured during the catheterization. The relationship between the peripheral venous and central venous pressures was assessed using simple linear regression and the Bland-Altman plot analysis for differences. Results: Thirty-eight adult Fontan patients (mean age 30.7 ± 8.5, range 18–52 years) undergoing 43 cardiac catheterizations were analyzed. The mean CVP was 17.3 +/− 4.7 mmHg. The mean PVP was 18.4 +/− 5 mmHg. CVP and PVP were highly correlated, with an R 2 value of 0.83 ( p  < 0.001). The CVP can be estimated with PVP measurements using the formula CVP = (0.86 * PVP) + 1.3. A Bland-Altman plot for PVP and CVP demonstrated that the PVP overestimated CVP by a mean of 1.2 mmHg, with a 95% limit of agreement of −5.2 mmHg to 2.8 mmHg. Conclusions: In adult Fontan patients, measuring PVP is a reliable, less-invasive, and accurate method of estimating the CVP during cardiac catheterization procedures. These findings may enable outpatient monitoring of Fontan hemodynamics. Highlights: Central venous pressure measurement in Fontan patients is invasive. Peripheral venous pressure (PVP) is a surrogate for central venous pressure (CVP). In Fontan patients, CVP can be estimated by PVP using: CVP = (0.86 * PVP) + 1.3.